Pengaruh Matakuliah Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Menjadi Wirausahawan dikalangan Mahasiswa Prodi Manajemen Angkatan 2023 Universitas Negeri Medan - Hasyim Hasyim; Afifah Nida Suhailah Boru Dalimunthe; Jekson Sihombing; Tasya Chintain Simanjuntak (LPPM Politeknik Pratama, 2026)
This study aims to examine the effect of Entrepreneurship Courses and Entrepreneurial Motivation on students Entrepreneurial Intention at Universitas Negeri Medan. The study employed a quantitative approach with a sample of 48 students and analyzed the data using multiple linear regression. The results show that, simultaneously, both variables have a positive and significant effect on entrepreneurial intention (F = 27.228; p < 0.001), with a coefficient of determination (R²) of 0.548. Partially, Entrepreneurship Courses have a positive and significant effect (β = 0.413; p = 0.008), while Entrepreneurial Motivation has a more dominant influence (β = 0.489; p < 0.001). These findings indicate that intrinsic motivation plays a more crucial role in enhancing students’ entrepreneurial intention, although entrepreneurship education also contributes positively.